Kurikulum Merdeka and Students’ Perceptions of Academic Freedom in Higher Education - Sinaga, Andromeda Valentino (Journal of Advance in Language, Literature, and Education, 2025)
This study aims to explore students' attitudes at Universitas Negeri Makassar toward academic freedom within the implementation of the Kurikulum Merdeka, particularly in the context of the Merdeka Belajar–Kampus Merdeka (MBKM) program. Employing a descriptive qualitative approach, data were gathered through semi-structured interviews. The findings reveal that students perceive an increased level of autonomy in selecting learning pathways aligned with their interests and needs, along with greater opportunities to actively participate in the learning process. However, institutional regulations and faculty policies continue to constrain the full realization of academic freedom. This study underscores the need for consistent policy support and structured guidance to foster a more effective implementation of academic freedom. The insights derived are expected to inform the development of higher education policies that are more responsive and student-centered.